Activation of liver X receptors protects oligodendrocytes in CA3 of stress-induced mice - Zhu, Peilin; Tang, Jing; Liang, Xin; Luo, Yanmin; Wang, Jin; Li, Yue; Xiao, Kai; Li, Jing; Deng, Yuhui; Jiang, Lin; Xiao, Qian; Qi, Yingqiang; et al. (Frontiers in Pharmacology, 2022)
Depression is a kind of complex disorder which has a various of structural abnormalities. Oligodendrocyte dysfunction is linked to the pathogenesis of depression and the promotion of hippocampal oligodendrocyte maturation and myelination could be a novel type of therapeutic of relieving depressive behaviors. Recent studies have pointed that activation of liver X receptors by GW3965 improved depressive phenotypes, but the effects of GW3965 on oligodendrocytes function and myelination in the hippocampus of depression remain relatively unclear. To address this issue, we investigated the effects of GW3965 on hippocampal mature oligodendrocytes and the myelin sheath of the mice subjected to chronic unpredictable stress (CUS). The behavioral tests were executed to assess the depressive behaviors. Then, the number of mature oligodendrocytes (CC1+) in each hippocampal subregions were precisely quantified through immunohistochemistry technique and stereological method, and the density of newborn mature oligodendrocyte (Brdu+/Olig2+/CC1+ cells) in each hippocampal subregions were counted with immunofluorescence. Besides, myelin basic protein (MBP) intensity was also measured by using immunofluorescence in the cornu ammonis 3 (CA3) region. We found that both the number of CC1+ oligodendrocytes and the density of the Brdu+/Olig2+/CC1+ cells were obviously decreased in each hippocampal subregion of the mice subjected to CUS, while four weeks of GW3965 treatment reversed these reductions only in the CA3 region. Meanwhile, the decrease of the intensity of MBP expression in the CA3 of the mice subjected to CUS were ameliorated by treatment with GW3965. Collectively, these results suggested that improvement of oligodendrocyte maturation and enhancement of the myelination may be structural mechanisms for the antidepressant effects of LXR agonist.